TOWARDS EVALUATING PAYMENT DISPUTE RESOLUTION MECHANISMS IN NIGERIAN BRANCHLESS BANKS - Okpako, Ejaita A.; Iyamah, Boyce E.; Ojie, Deborah V.; Okperigho, Samuel U.; Chiemeke, Stella C. (FUDMA Journal of Sciences, 2025)
Branchless banking has expanded financial access in Nigeria by enabling millions of users to complete transfers, airtime purchases, bill payments, and merchant transactions without visiting traditional bank branches. While this innovation advances financial inclusion, it also creates recurring challenges such as failed transfers, duplicate debits, delayed reversals, and weak dispute management that undermine user trust. This study evaluates dispute resolution in three leading branchless banks Opay, Palmpay, and Moniepoint focusing on effectiveness, responsiveness, and user satisfaction. A purposive sample of fifty users with experience of payment disputes was surveyed to capture dispute types, reporting channels, resolution timelines, and perceptions of service quality. Expectation Confirmation Theory and SERVQUAL dimensions of responsiveness and reliability provided the analytical framing. Findings indicate that disputes were usually resolved within three days, though experiences varied across platforms. Palmpay recorded the highest satisfaction levels, Opay was rated most responsive, while Moniepoint performed weakest overall. The study highlights gaps in communication and transparency, recommending harmonised resolution timelines and stronger regulatory oversight to sustain trust in Nigeria’s digital financial services